2022
DOI: 10.1111/imj.15086
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient usage of faecal calprotectin in a tertiary hospital

Abstract: Background: Faecal calprotectin (FCP) is a highly sensitive non-invasive marker of intestinal inflammation that has evidence-based roles in outpatient diagnosis and management of inflammatory bowel disease.Aims: To examine indications for FCP in a tertiary inpatient population and its role in inpatient management and subsequent investigations.Methods: An electronic database was used to identify all patients over the age of 18 years who had FCP performed during a hospital admission over a 3-year period from Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Barnes et al reported that fecal calprotectin levels rarely changed inpatient management and had no significant difference in the usage of subsequent diagnostic colonoscopy. 17 The strength of this study is that our data were prospectively collected. Moreover, there was no bias in data collection because fecal calprotectin level was not measured until the end of the study after all clinical data had been collected.…”
Section: Discussionmentioning
confidence: 99%
“…Barnes et al reported that fecal calprotectin levels rarely changed inpatient management and had no significant difference in the usage of subsequent diagnostic colonoscopy. 17 The strength of this study is that our data were prospectively collected. Moreover, there was no bias in data collection because fecal calprotectin level was not measured until the end of the study after all clinical data had been collected.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of medications, particularly anti-inflammatory drugs, immunosuppressants, and biologicals, such as anti-tumor necrosis factor agents, should be determined in future work. Finally, fecal calprotectin has emerged as a minimally invasive biomarker for disease activity in IBD ( 58 ). Although fecal calprotectin was not routinely collected in the current patient cohort, additional studies could investigate the relationship of cDPP enzyme activity to fecal calprotectin levels.…”
Section: Discussionmentioning
confidence: 99%